A computer based simulator for Erbium-Doped Fiber Amplifier - Naji, Ahmed Wathik; Akhter, Fowzia; Ibrahimy, Muhammad Ibn; Hamida, Belal Ahmed; Mahdi, M. A.; Siddiquei, Hasin Reza (2010)
This paper presents new open source computer based simulator for the implementation of single stage Erbium-Doped Fiber Amplifier (EDFA) such as single pass (SP), double pass (DP) and triple pass (TP) EDFA. In this software it is possible to manipulate the design parameters such as pump power, pump wavelength, signal power, signal wavelength, fiber length, doping concentration etc. and based on the design parameters, the performance parameters i.e. gain and noise figure will be shown on the display. The proposed simulator has been developed by using the mathematical model of EDFAs. The working principle of this software has been explained in this paper. Matlab GUI has been used to design the proposed software.